Increasing quantity without compromising quality: How managerial framing affects intrapreneurship - Rigtering, J.P.C. (Coen); Weitzel, G.U. (Utz); Muehlfeld, K. (Katrin) (Journal of Business Venturing, 2019)
Individual-level opportunity recognition processes are vital to corporate entrepreneurship. However, little is known regarding how managerial communication impacts the effectiveness of idea suggestion systems in stimulating individuals' participation in intrapreneurial ideation. Integrating self-determination theory, creativity, and framing research, we theorize how different ways of inviting employees to submit proposals (opt-out/opt-in registration; provision of examples) affect the number and quality of submitted ideas. Our multi-method study (field experiment, vignette experiment, interviews) shows that (i) opt-out increases employee participation without reducing idea quality and (ii) the provision of examples enhances the usefulness of ideas but decreases novelty and the number of submissions.